Preparation of Extruded Snacks with Flavored Flour Obtained from the Carcasses of Nile Tilapia: Physicochemical, Sensory, and Microbiological Analysis. Issue 3 (16th March 2017) - Justen, Alex P.; Souza, Maria Luiza Rodrigues de; Monteiro, Antonio R. G.; Mikcha, Jane M. G.; Gasparino, Eliane; Delbem, Ádina B.; de Carvalho, Maria Regina B.; Del Vesco, Ana P.
ABSTRACT: This study aimed to develop extruded snacks including flour obtained from Nile tilápia carcasses, and then evaluate the chemical composition, colorimetry, thiobarbituric acid reactive substances, and microbiology. There was a significant increase in the levels of crude protein, ether extract, ash, and minerals, as well as a reduction in carbohydrates as more flour was included in the snacks. Increased levels of flavored flour caused reduction in the brightness of snacks. Oxidative rancidity was not detected in snacks. The inclusion of flour improved the nutritional value of extruded snacks without changing sensory characteristics. Microbiologically, the snacks are suitable for human consumption.